RIAP DIAMETER TANAMAN MERANTI PADA SISTEM SILVIKULTUR TEBANG PILIH TANAM INDONESIA (TPTI) DAN TEBANG PILIH TANAM JALUR (TPTJ) DI AREAL IUPHHK-HA PT. SUKA JAYA MAKMUR KABUPATEN KETAPANG KALIMANTAN BARAT - Selfiany, Widiya Octa; Muin, Abdurrani; AM, Iskandar (JURNAL HUTAN LESTARI, 2017)
Area of IUPHHK-HA PT. Suka Jaya Makmur has planted three types of Shorea (Shorea leprosula, Shorea parvifolia, and Shorea johoriensis) at silvicultural system TPTI and TPTJ. The present study aimed at identifying the diameter increment of Shorea leprosula, Shorea parvifolia, and Shorea johoriensis which were planted by using silvicultural system of Indonesian Selective Logging and Plantation (TPTI) and Selective Logging and Line Planting (TPTJ). Data collection was done through a technique called purposive sampling. Results of the discussion showed that the diameter increment of Shorea leprosula was bigger than two other types of Shorea i.e. Shorea parvifolia and Shorea johoriensis. The analysis also revealed that there was a difference of the diameter increment between silvicultural system of TPTI and TPTJ. The diameter of TPTJ increased faster i.e. 3.46 cm/year in comparison with TPTI which was only 1.02 cm/year. Keywords: diameter increment, silvicultural system TPTI and TPTJ, three types of Shorea.